A vector for Aspergillus transformation conferring phleomycin resistance. - I. E. Mattern; P. J. Punt; C. A.M.J.J. Van den Hondel (Fungal Genetics Reports, 1988)
Recently, transformation of Aspergillus species with vector pAN7-1, conferring resistance to hygromycin B was reported (Punt et al. 1987 Gene 56:117-124).